If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -8) + -3(9x + -11) = 5(2x + -3) + -12 Reorder the terms: 4(-8 + 5x) + -3(9x + -11) = 5(2x + -3) + -12 (-8 * 4 + 5x * 4) + -3(9x + -11) = 5(2x + -3) + -12 (-32 + 20x) + -3(9x + -11) = 5(2x + -3) + -12 Reorder the terms: -32 + 20x + -3(-11 + 9x) = 5(2x + -3) + -12 -32 + 20x + (-11 * -3 + 9x * -3) = 5(2x + -3) + -12 -32 + 20x + (33 + -27x) = 5(2x + -3) + -12 Reorder the terms: -32 + 33 + 20x + -27x = 5(2x + -3) + -12 Combine like terms: -32 + 33 = 1 1 + 20x + -27x = 5(2x + -3) + -12 Combine like terms: 20x + -27x = -7x 1 + -7x = 5(2x + -3) + -12 Reorder the terms: 1 + -7x = 5(-3 + 2x) + -12 1 + -7x = (-3 * 5 + 2x * 5) + -12 1 + -7x = (-15 + 10x) + -12 Reorder the terms: 1 + -7x = -15 + -12 + 10x Combine like terms: -15 + -12 = -27 1 + -7x = -27 + 10x Solving 1 + -7x = -27 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 1 + -7x + -10x = -27 + 10x + -10x Combine like terms: -7x + -10x = -17x 1 + -17x = -27 + 10x + -10x Combine like terms: 10x + -10x = 0 1 + -17x = -27 + 0 1 + -17x = -27 Add '-1' to each side of the equation. 1 + -1 + -17x = -27 + -1 Combine like terms: 1 + -1 = 0 0 + -17x = -27 + -1 -17x = -27 + -1 Combine like terms: -27 + -1 = -28 -17x = -28 Divide each side by '-17'. x = 1.647058824 Simplifying x = 1.647058824
| 51x1/4= | | (2x+7)(x-3)(x+3)(2x+5)=91 | | X^3-7x+y=1 | | 33.000/00 | | (8x+1)=(15x+10) | | 5x+1y+.05z=100 | | 2x=33-4x | | 2n+3+5+7= | | 400+x=977 | | 30x+20y=5930 | | log2/log1.15 | | x(x-4)-4=0 | | an=n-3 | | 600=.30x | | 8=2k+2k | | 299=332-x | | 3x+18+2y=0 | | 813/4= | | 8x=-46 | | 121=73+x | | 10=0.82x | | 127-x=54 | | h(t)=-4.9t^2+5.9t+2 | | 13+19=z+5 | | 2x+24y=x | | p=-3+5c | | 3/5m=-8/7 | | 16=6+c | | e-5=17+3 | | 17p+12=10p-13 | | 5*5*5=/=500 | | X+77=81 |